PENGARUH KONSENTRASI BORAKS PADA PENGAWETAN KAYU TUMIH (Combretocarpus rotundatus (Miq.) Danser) DALAM KETAHANANNYA TERHADAP SERANGAN RAYAP KAYU KERING (Cryptotermes cynocephalus Light.) - Wahyu Supriyati; Gloria Putri Novelia M; Yanciluk; Alpian (Agrienvi: Jurnal Ilmu Pertanian, 2021)
Tumih wood (Combretocarpus rotundatus (Miq.) Danser) was found abundanly in Central Kalimantan but only has durable class 3. The preservation needed to extend the life service of the wood. The aims of this research was to know the effect of borax preservatives at various concentrations to the retention of Tumih wood, to know the mortality of dry wood termite (Cryptotermes cynocephalus Light) and weight loss of the tumih wood against the termite. Wood testing against drywood termites reffer to the Indonesian National Standard (SNI 01-2707-2006). Data analysis using a Completely Randomized Design (CRD) of 4 concentrations and 3 replications. The result showed that concentration has significant effect on retention. The highest retention value was found at concentration of 7% (B3) that was 10,34 kg/m3. Preservative concentration had a significant effect to termite mortality. The concentration of 3% was able to against the termite attacks on Tumih wood (mortality value was 93,3%). Concentration has not significant effect to the weight loss of Tumih wood